Strategies Employed in Answering LMS Activities as an Academic Habit of Grade 12 HUMSS Students in Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The pandemic has distraught the Education Sector globally. Consequently, new normal learning was implemented. The Learning Management System (LMS) is a platform for online academic activities. And because of its integration, the students are now forced to shift from traditional school activities to online activities. The strategies that the students have built from traditional learning and answering activities may also be disrupted because of this shift. This study aimed to determine the strategies that can be employed in answering LMS online activities as an academic habit of grade 12 HUMSS students of Bestlink College of the Philippines. This research study used Qualitative methods and a Descriptive Research Design to obtain a general overview of the topic. Online survey questionnaires were used as the research instrument for data collection. The convenience sampling technique was used in choosing sixty (60) respondents. The study found that some students experienced inconvenience and challenges in building their strategies since the shift to the new normal education system. Distractions, LMS system errors, poor management skills, and unfinished outputs are some of them. Furthermore, the students agree to the different new strategies that can be employed in answering their LMS online activities and favour adopting these recommended beneficial strategies. Students should motivate themselves, incorporate time and priority management, and always remember that LMS activities are part of academics. Teachers also have a role in boosting their students’ motivation and encouragement.
Keywords: Academic Habits; Activities; Habits; LMS; Strategies